Blockade of vascular endothelial growth factor receptor 2 inhibits intraplaque haemorrhage by normalization of plaque neovessels. (7th September 2018) - de Vries, M. R.; Parma, L.; Peters, H. A. B.; Schepers, A.; Hamming, J. F.; Jukema, J. W.; Goumans, M. J. T. H.; Guo, L.; Finn, A. V.; Virmani, R.; Ozaki, C. K.; Quax, P. H. A.
Abstract: Background: Plaque angiogenesis is associated with atherosclerotic lesion growth, plaque instability and negative clinical outcome. Plaque angiogenesis is a natural occurring process to fulfil the increasing demand of oxygen and nourishment of the vessel wall. However, inadequate formed, immature plaque neovessels are leaky and cause intraplaque haemorrhage. Objective: Blockade of VEGFR2 normalizes the unbridled process of plaque neovessel formation and induces maturation of nascent vessels resulting in prevention of intraplaque haemorrhage and influx of inflammatory cells into the plaque and subsequently increases plaque stability. Methods and Results: In human carotid and vein graft atherosclerotic lesions, leaky plaque neovessels and intraplaque haemorrhage co‐localize with VEGF/VEGFR2 and angiopoietins. Using hypercholesterolaemic ApoE3*Leiden mice that received a donor caval vein interposition in the carotid artery, we demonstrate that atherosclerotic vein graft lesions at t28 are associated with hypoxia, Hif1α and Sdf1 up‐regulation. Local VEGF administration results in increased plaque angiogenesis. VEGFR2 blockade in this model results in a significant 44% decrease in intraplaque haemorrhage and 80% less extravasated erythrocytes compared to controls. VEGFR2 blockade in vivo results in a 32% of reduction in vein graft size and more stable lesions with significantly reduced macrophage content (30%), and increased collagen (54%) and smooth muscle cell content (123%). Significant decreased VEGF, angiopoietin‐2 and increased Connexin 40 expression levels demonstrate increased plaque neovessel maturation in the vein grafts. VEGFR2 blockade in an aortic ring assay showed increased pericyte coverage of the capillary sprouts. Conclusion: Inhibition of intraplaque haemorrhage by controlling neovessels maturation holds promise to improve plaque stability. Abstract :